Medicinal plants used in Jeddah, Saudi Arabia: A gender perspective. (15th July 2020) - Alqethami, Afnan; Aldhebiani, Amal Y.; Teixidor-Toneu, Irene
Abstract: Ethnopharmacological relevance: Very few studies examining quantitatively gender differences in the knowledge and use of medicinal plants exist for the Arab world. Differences in ethnobotanical knowledge of medicinal plants between men and women in Jeddah are explored here for the first time. Aim of the study: Our study aims to document urban medicinal plant knowledge in Jeddah, and to answer the following questions: (1) What medicinal plants are used by Saudis in Jeddah? (2) To what extent do men and women use medicinal plants? (3) Are plants used by men significantly different to those used by women? And, (4) do men and women learn about medicinal plants in different ways? Given the gendered nature of space and relations in the Arab world, we hypothesise that men and women learn about plants in different ways and that this will contribute to explain any possible differences. Materials and methods: Ethnobotanical fieldwork took place in Jeddah from August 2018 to September 2019. Individual free-listing, semi-structured interviews and an online survey questionnaire were carried out to document local medicinal plant. In total, 50 men and 50 women were interviewed face-to-face and 344 people responded to the questionnaire, of which 154 were men and 190 were women. Results: A total of 94 medicinal plant vernacular names were documented representing 85 different plant species belonging to 37 families. Men cited 63 plants (33 plant families) and women 83 (36 plant families). Sixty-one plants were cited by both men and women, two only by men and 22 only by women. Men and women learn in similar ways, but generally use medicinal plants to treat different ailments. Women rely on medicinal plant use to a larger extent. Conclusion: Medicinal plant use is dependent on gendered social roles and experience, as well as preference for biomedicine or medicinal plant use. Men and women use similar plants, but women have greater knowledge that increases with age. Given the food-medicine continuum, women's double role of family food and care providers may explain their expertise in medicinal plant use. Graphical abstract: Image 1